2017
DOI: 10.1038/s41598-017-07201-z
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of accelerated development and enhanced growth on oxidative stress and telomere shortening in amphibian larvae

Abstract: Organisms react to environmental changes through plastic responses that often involve physiological alterations with the potential to modify life-history traits and fitness. Environmentally induced shifts in growth and development in species with complex life cycles determine the timing of transitions between subsequent life stages, as well as body condition at transformation, which greatly determine survival at later stages. Here we show that spadefoot toad larvae surviving pond drying and predators experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 69 publications
4
71
1
Order By: Relevance
“…Pacific horned frogs showed one of the widest range of sizes at metamorphosis reported for any amphibian in their natural population, individuals differing by up to 100% in body size and 890% in body mass. This range is broader than previously reported intrapopulation variation in the literature [31,43]. Pond permanence [30], food availability [44], temperature [45] and presence of predators or competitors [46,47] are known to have a profound effect on individual metamorphosing size in anurans, and the interaction between various selective pressures can determine a large spectrum of sizes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Pacific horned frogs showed one of the widest range of sizes at metamorphosis reported for any amphibian in their natural population, individuals differing by up to 100% in body size and 890% in body mass. This range is broader than previously reported intrapopulation variation in the literature [31,43]. Pond permanence [30], food availability [44], temperature [45] and presence of predators or competitors [46,47] are known to have a profound effect on individual metamorphosing size in anurans, and the interaction between various selective pressures can determine a large spectrum of sizes.…”
Section: Discussionmentioning
confidence: 73%
“…However, a higher than optimal growth rate comes at a fitness cost, reflected in decreased survival [37]. Along with ecological factors, such as increased exposure to predators and competitors because of prolonged foraging [38], several other components can contribute to the lower fitness associated with accelerated growth rates, amongst which a lower resistance to starvation because of intense metabolism and low lipid reserves [40], delayed ossification [41], depressed immunological function [42], or cellular oxidative stress [43]. Some of the intrinsic costs mentioned above might have contributed to the observed higher mortality in the froglets that had metamorphosed at a small size in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Intense cellular oxidative stress often shortens telomeres; however, the levels of redox changes detected in larvae showing compensating growth responses may not be enough to produce DNA damages, be tissue‐dependent or even be only apparent later in life. Previous studies in amphibians found shorter telomeres in tadpoles surviving predators and maintaining high growth rates (Burraco, Díaz‐Paniagua, & Gomez‐Mestre, ), or in tadpoles developing faster against permanent desiccation risk (Burraco, Valdés, Johansson, & Gomez‐Mestre, ). The lack of telomere shortening observed in our study can be also a consequence of the life history of the R. temporaria population used in this experiment.…”
Section: Discussionmentioning
confidence: 91%
“…We then measured female telomere length, offspring telomere length, and body size soon after birth. There is evidence that the predator presence or predation attempts can have an effect on telomere length of the exposed individuals (Burraco, Díaz-Paniagua, & Gomez-Mestre, 2017;Kärkkäinen et al, 2019;McLennan et al, 2016;Olsson, Pauliny, Wapstra, & Blomqvist, 2010), thus suggesting that both females and offspring telomere length will be affected. However, no study has experimentally investigated the effect of the perception of predation risk on both female and offspring telomere length.…”
mentioning
confidence: 99%